2021
DOI: 10.3390/su131810025
|View full text |Cite
|
Sign up to set email alerts
|

How Retailer Co-Opetition Impacts Pricing, Collecting and Coordination in a Closed-Loop Supply Chain

Abstract: The cooperative and competitive (i.e., co-opetition) behavior between retailers plays a significant role in the development of operations and marketing strategies in a supply chain. Specifically, retailers’ co-opetition relationship pivotally influences the sustainable performance in a closed-loop supply chain. This study examines the impact of retailer co-opetition on pricing, collection decisions and coordination in a closed-loop supply chain with one manufacturer and two competing retailers. Based on observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Yang, W et al (2022) studied the co-opetition strategy between the manufacturer of a proprietary component (MPC) and the original equipment manufacturer (OEM), analyzed the optimal cooperation strategy of MPC, and showed that the existence of third-party suppliers was the key factor in their competition and cooperation behavior through the model [17]. Li, X et al (2021) found that the retailer's profit was the largest under the Bertrand competition mode through the equilibrium solution by establishing the centralized and decentralized game-theoretic models under the Bertrand competition, Stackelberg competition, and collusion competition modes [18]. Co-opetition behavior is rarely included in research on the pharmaceutical supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang, W et al (2022) studied the co-opetition strategy between the manufacturer of a proprietary component (MPC) and the original equipment manufacturer (OEM), analyzed the optimal cooperation strategy of MPC, and showed that the existence of third-party suppliers was the key factor in their competition and cooperation behavior through the model [17]. Li, X et al (2021) found that the retailer's profit was the largest under the Bertrand competition mode through the equilibrium solution by establishing the centralized and decentralized game-theoretic models under the Bertrand competition, Stackelberg competition, and collusion competition modes [18]. Co-opetition behavior is rarely included in research on the pharmaceutical supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to implement the "Circular Economy Promotion Law" and promote a resourcesaving and environment-friendly society, as early as 2010, the National Development and MSCRA 6,2 Reform Commission of China indicated that remanufacturing is an advanced form of "reuse" in the circular economy. However, researches on remanufacturing usually focus on product recycling channels and strategies (Pal and Sarkar, 2021;Pan and Lin, 2021), product pricing decision and coordination (Lang and Jia, 2021;Li et al, 2021a, b), emission reduction and technologies (Chen et al, 2022;Li et al, 2021a, b;Yilmaz et al, 2021), and so on, but relatively little on the sales of remanufactured products.…”
Section: Introductionmentioning
confidence: 99%
“…However, researches on remanufacturing usually focus on product recycling channels and strategies (Pal and Sarkar, 2021; Pan and Lin, 2021), product pricing decision and coordination (Lang and Jia, 2021; Li et al. , 2021a, b), emission reduction and technologies (Chen et al ., 2022; Li et al. , 2021a, b; Yilmaz et al ., 2021), and so on, but relatively little on the sales of remanufactured products.…”
Section: Introductionmentioning
confidence: 99%
“…Experts agree that transforming agri-food supply chains into sustainable systems requires a coordinated approach along the chain (Raimondo et al, 2021). Coordination aims at improving joint performance by aligning individual actors' strategies (Li et al, 2021) and a lack of coordination complicates the achievement of shared objectives (Dries & Swinnen, 2007). Chain coordination is therefore seen as a prerequisite for promoting sustainability-oriented performance in supply chains.…”
Section: Introductionmentioning
confidence: 99%